2023
DOI: 10.1111/cyt.13279
|View full text |Cite
|
Sign up to set email alerts
|

Delphi expert consensus for whole slide imaging in thyroid cytopathology

Stefano Marletta,
Maria Salatiello,
Liron Pantanowitz
et al.

Abstract: ObjectiveDespite an increase in thyroid fine needle aspiration (FNA) and advances in whole slide imaging (WSI) adoption, digital pathology is still considered inadequate for primary diagnosis of these cases. Herein, we aim to validate the utility of WSI in thyroid FNAs employing the Delphi method strategy.MethodsA panel of experts from seven reference cytology centres was recruited. The study consisted of two consecutive rounds: (1) an open‐ended, free‐response questionnaire generating a list of survey items; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Recently, innovative research, including whole slide imaging and digital pathology, has been effectively improving cytopathology diagnosis. [21][22][23] In addition, multiple guidelines suggest that molecular testing of Bethesda III and IV samples could effectively improve the sensitivity of the preoperative diagnosis of thyroid nodules. 24,25 Therefore, reducing the proportion of Bethesda III specimens and developing molecular testing are effective ways to improve the diagnostic value of US-FNAB.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, innovative research, including whole slide imaging and digital pathology, has been effectively improving cytopathology diagnosis. [21][22][23] In addition, multiple guidelines suggest that molecular testing of Bethesda III and IV samples could effectively improve the sensitivity of the preoperative diagnosis of thyroid nodules. 24,25 Therefore, reducing the proportion of Bethesda III specimens and developing molecular testing are effective ways to improve the diagnostic value of US-FNAB.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are other situations in which FS can play an important role such as transplantation: donors show the same prevalence of thyroid nodules as the general population. Although recent literature showed a higher accuracy for FNB based on the current techniques ( 25 ), digital pathology will possibly help in the future reducing FS time and increase precision ( 26 , 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies reported that artificial intelligence algorithms allow for precise quantification of features such as nuclear area and elongation factor or crowding of nuclei, which appear to be differently distributed between benign and malignant nodules, revealing the potential to efficiently evaluate FNA cytology cases ( 36 ). The whole slide imaging, a digital pathology modality, facilitates the use of artificial intelligence in the field of pathology ( 37 ). In the future study, we will develop an artificial intelligence model with multidimensional features including radiological images, clinical indicators, genetic features, and pathological features to reduce the indeterminate diagnosis of patients with TNs, especially for organ donors who might contribute to the transmission of thyroid cancer ( 38 ).…”
Section: Discussionmentioning
confidence: 99%